2017
DOI: 10.1111/jcmm.13123
|View full text |Cite
|
Sign up to set email alerts
|

The activity of the carbamoyl phosphate synthase 1 promoter in human liver‐derived cells is dependent on hepatocyte nuclear factor 3‐beta

Abstract: Carbamoyl phosphate synthase 1 (CPS1) is the rate‐limiting enzyme in the first step of the urea cycle and an indispensable enzyme in the metabolism of human liver. However, CPS1 epigenetic regulation involves promoter analysis and the role of liver‐enriched transcription factors (LETFs), which is not fully elucidated. In this work, the promoter region of hCPS1 gene was cloned, and its activity was investigated. An LETF, hepatocyte nuclear factor 3‐beta (HNF3β), was found to promote the transcriptional expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…CPS1 overexpression is associated with poor prognosis in several types of cancer, such as colon cancer, cholangiocarcinoma and glioblastoma . CPS1 has also been reported to be regulated by hepatocyte nuclear factor 3β (HNF3β) and sirtuin 5 (SIRT5) by their transcriptional activation or deacetylation‐ and deglutarylation‐mediated activation . Thus, the results of our study might supplement the previous reported associations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…CPS1 overexpression is associated with poor prognosis in several types of cancer, such as colon cancer, cholangiocarcinoma and glioblastoma . CPS1 has also been reported to be regulated by hepatocyte nuclear factor 3β (HNF3β) and sirtuin 5 (SIRT5) by their transcriptional activation or deacetylation‐ and deglutarylation‐mediated activation . Thus, the results of our study might supplement the previous reported associations.…”
Section: Discussionsupporting
confidence: 84%
“…[30][31][32] CPS1 has also been reported to be regulated by hepatocyte nuclear factor 3β (HNF3β) and sirtuin 5 (SIRT5) by their transcriptional activation or deacetylation-and deglutarylation-mediated activation. [33][34][35] Thus, the results of our study might supplement the previous reported associations.…”
Section: Abnormal and Ectopic Cps1 Expression In Tumour Cells May Leadsupporting
confidence: 86%
“…However, the two species have different metabolic rates due to their different sizes and regulation of the CPS1 gene and urea cycle may differ in the two organisms. More recently, a region of the human CPS1 gene that corresponds to the rat Cps1 promoter and proximal enhancer has been shown to bind HNF3 and direct reporter gene expression in hepatoma cells [64]. Human CPS1 gene is located on chromosome 2, band 2q34 where it spans approx.…”
Section: Transcriptional Regulation Of Mammalian Cps1 Genementioning
confidence: 99%
“…Although related to PGC-1α, PGC-1β was also assessed as it is known to be targeted in the Hif-1α-mediated suppression of lcad and mcad . The ppara, hepatocyte nuclear factor-3-beta (hnf3b), and hepatocyte nuclear factor-4-alpha (hnf4a) genes, known to promote the expression of acyl-CoA dehydrogenases and urea cycle enzymes, were measured to better understand how the cells of dehydrated X. laevis were regulating the expression of metabolic transcription factors during dehydration (Chen et al, 2017;Inoue et al, 2002;Mandard et al, 2004;Wolfrum and Stoffel, 2006). Overall, this chapter provided evidence that PGC-1α and Hif-1α are important metabolic regulators in X. laevis dehydration which resulted in the remodelling of genes that is suggestive of increased glycolysis and decreased fatty acid oxidation.…”
Section: Chapter Objectivementioning
confidence: 99%
“…To further understand the molecular signaling pathways that may be contributing to urea cycle activation, mRNA transcript levels of hnf3b and hnf4a as well as cps1 and otc were quantified in liver. The hepatocyte nuclear factors HNF3β and HNF4α are transcription factors that induce the mRNA expression of cps1 and otc by binding to their respective promoter regions (Chen et al, 2017;Inoue et al, 2002). Although otc was unchanged, mRNA levels of cps1 increased in the liver of dehydrated X. laevis, demonstrating that increases in urea cycle genes contribute to the broader dehydration response.…”
Section: Regulation Of Ureagenesis By Pgc-1αmentioning
confidence: 99%